If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3 + 4) + -3(r + 1) = 11 Combine like terms: 3 + 4 = 7 2(7) + -3(r + 1) = 11 Multiply 2 * 7 14 + -3(r + 1) = 11 Reorder the terms: 14 + -3(1 + r) = 11 14 + (1 * -3 + r * -3) = 11 14 + (-3 + -3r) = 11 Combine like terms: 14 + -3 = 11 11 + -3r = 11 Add '-11' to each side of the equation. 11 + -11 + -3r = 11 + -11 Combine like terms: 11 + -11 = 0 0 + -3r = 11 + -11 -3r = 11 + -11 Combine like terms: 11 + -11 = 0 -3r = 0 Solving -3r = 0 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Divide each side by '-3'. r = 0 Simplifying r = 0
| 1800-2400x=0 | | 10(e+5)=340 | | 6x-1-4(x+1)=6x+4 | | 5x-9=-3x-12+5x | | 5x-9=-3x-12 | | 12(x-2)=148 | | 2x^2=1296 | | 2(1s+3)+(4s-5)=1s | | 6(m-15)=-4m | | 1/3n+3=n-2 | | m^2-14m=49 | | 75=-3(m+3)+1m | | 75=-3(m+3)+m | | 2.50x+5x=625 | | 42=-3(m+6)+1m | | 20-6x=4x-15 | | 2a-4x=a | | 2y(3y-z)= | | 4(x-2)=9-x | | -6-7y=10 | | 20-2x=80-4y | | 1x(x+2)=6(x+12) | | 36x^2=49y^2 | | 8a(5a-2b)= | | (X+3)2=81 | | 2x^2=-4p+3 | | 5y+10=y-3 | | 45.87(x+3)=60.54 | | 1/3=1/4d | | 1/3d=1/4 | | 30=x-12 | | 7x-16-8x=14 |